Changes in Serum Neutralizing Antibodies Levels During Convalescence of COVID-19 Patients - Chen, Qing-Qing; Gong, Lei; Wu, Xiao-Min; Feng, Ya-Ting; Luo, Wan-Rong; Zhou, Xue; Yuan, Yuan; Yu, Jun-Ling; He, Lan; Wang, Peng; Ge, Ying-Lu; Hou, Sai; et al. (Frontiers in Medicine, 2022)
Detection of serum-specific SARS-CoV-2 antibody has become a complementary means for the identification of coronavirus disease 2019 (COVID-19). As we already know, the neutralizing antibody titers in patients with COVID-19 decrease during the course of time after convalescence, whereas the duration of antibody responses in the convalescent patients has not been defined clearly. In the current study, we collected 148 serum samples from 37 confirmed COVID-19 cases with different disease severities. The neutralizing antibodies (Nabs), IgM and IgG against COVID-19 were determined by CLIA Microparticle and microneutralization assay respectively. The time duration of serum titers of SARS-CoV-2 antibodies were recorded. Our results indicate that IgG (94.44%) and Nabs (89.19%) can be detected at low levels within 190-266 days of disease onset. The findings can advance knowledge regarding the antibody detection results for COVID-19 patients and provide a method for evaluating the immune response after vaccination.